SPLASH: the Southern Parkes Large-Area Survey in Hydroxyl – data description and release. Issue 3 (14th March 2022) - Dawson, J R; Jones, P A; Purcell, C; Walsh, A J; Breen, S L; Brown, C; Carretti, E; Cunningham, M R; Dickey, J M; Ellingsen, S P; Gibson, S J; Gómez, J F; et al.
ABSTRACT: We present the full data release for the Southern Parkes Large-Area Survey in Hydroxyl (SPLASH), a sensitive, unbiased single-dish survey of the Southern Galactic Plane in all four ground-state transitions of the OH radical at 1612, 1665, 1667, and 1720 MHz. The survey covers the inner Galactic Plane, Central Molecular Zone, and Galactic Centre over the range | b | < 2°, 332^° l 10°, with a small extension between 2^° b 6°, 358^° l 4°. SPLASH is the most sensitive large-scale survey of OH to-date, reaching a characteristic root-mean-square sensitivity of ∼15 mK for an effective velocity resolution of ∼0.9 km s −1 . The spectral line datacubes are optimized for the analysis of extended, quasi-thermal OH, but also contain numerous maser sources, which have been confirmed interferometrically and published elsewhere. We also present radio continuum images at 1612, 1666, and 1720 MHz. Based on initial comparisons with 12 CO( J = 1–0), we find that OH rarely extends outside CO cloud boundaries in our data, but suggest that large variations in CO-to-OH brightness temperature ratios may reflect differences in the total gas column density traced by each. Column density estimation in the complex, continuum-bright Inner Galaxy is a challenge, and we demonstrate how failure to appropriately model sub-beam structure and the line-of-sight source distribution can lead to order-of-magnitude errors. Anomalous excitation of the 1612 and 1720 MHz satellite lines is ubiquitous in the inner Galaxy, but is disabled by line overlap in and around the Central Molecular Zone.